Epidemiology and genetic analysis of Oestrus ovis from slaughtered sheep in Sulaymaniyah province, Iraq - Mohammed Aram Ahmad; Soor Taib Ahmed Hama (Journal of Veterinary Research)
Oestrosis is a type of nasal myiasis that is caused by larvae of flies from the Oestrus genus and is a disease of economic significance in small ruminants. The research aimed to investigate the prevalence of oestrosis and detect differences in the COX1 gene among haplotypes found in Sulaymaniyah, in the Kurdistan region of Iraq.